Kadar Glukosa Darah dan Infestasi Ektoparasit Flagellata pada Ikan Mas Koki (Carrasius auratus) yang diberi Suspensi Whole Cell Lernaea dengan Dosis dan Waktu Pemeliharaan yang Berbeda - Netty Sreani; Laksmi Sulmartiwi; Gunanti mahasri (Airlangga University, 2023)
The high consumer interest in ornamental fish such as goldfish causes aquaculture to try to meet the highest production so that large scale aquaculture activities appear accompanied by problems due to imbalances between the host, the environment and diseases such as pathogens. The purpose of this study was to determine the effect of giving Whole Cell Lernaea as an immunostimulant development material as an effort to prevent pathogen attacks in aquaculture. This study used a completely randomized design (CRD) with a factorial pattern, namely factor A was different doses of Whole cell Lernaea and factor B was different length of maintenance. The results showed that the highest blood glucose levels of goldfish occurred in the 0 ppm treatment on day 0 with a range between 53.60-87.60 mg/dL and the lowest in the 5 ppm treatment on day 21 with a range between 44.20-86.60 mg/dL. Ichthyobodo spp. ectoparasite infestation. occurred on days 0 and 14 with a dose of 0 ppm which is about 2-3 ind/head different from giving a dose of 5 ppm during maintenance for 21 days there were no cases of goldfish that were attacked by ectoparasites. There was an interaction between dose and duration of maintenance on blood glucose levels of goldfish given Whole cell lernaea suspension, while there was no interaction with flagella ectoparasite infestation. The best treatment to reduce blood glucose levels to normal is the administration of Whole Cell Lernaea suspension at a dose of 5 ppm and a maintenance time of 21 days.